KUALITAS BIBIT RAMIN (Gonystylus bancanus (Miq). Kurz) UNTUK PENANAMAN PENGAYAAN AREAL BEKAS TEBANGAN (Ramin (Gonystylus bancanus (Miq). Kurz) seedling quality for enrichment planting of logged over area) - Abdurrani Muin (Universitas Tanjungpura, 2011)
Enrichment planting in logged-over area needs high-quality seedlings that have high competitiveness, when planted around or near to other plants that grow naturally. The aim of this study is to find techniques to produce high-quality ramin seedlings. The studie employr the following experimental methods : 1) split plot in time to study the arbuscular mycorrhizal fungi (AMF) colonization in roots of natural regeneration of ramin, 2) completely randomized design to study the growth of ramin seedlings in the nursery, 3) randomized block design to study plant growth of ramin at logged-over area. The results show that AMF colonization in the root of ramin seedlings taken from the field was highest at medium light intensity. Meanwhile, the optimum light intensity to raise mycorrhizal seedlings in the nursery is 55 % to 75 %. The AMF colonization increased height and diameter growth, fresh and dry weights, macro-nutrients absorption, dependency of P uptake (DPU), shoot-root ratio quality and index of ramin seedling in the nursery. Ramin is highly dependent on AMF having a relative mycorrhizal dependency (RMD) of more than 50 % and percent growth relative (PGR) of more than 100 %. Rock phosphate of 50 g/polybag is sufficient to support the growth of mycorrhizal seedlings in the nursery. The AMF colonization increases height and diameter of ramin seedlings after being planted in the field (logged-over area). It could be concluded that high quality ramin seedlings could be produced by inoculation of AMF under optimum light intensity and optimum dosage of rock phosphate.Key words : ramin (G. bancanus), light intensity, arbuscular mychorrhizal fungi (AMF), rock phosphate